Folic acid allergy and the role of the basophil activation test - Gouveia,Joana (2024)
ABSTRACT Background: Despite the large use of folic acid supplements, there are very few cases of reported allergy. Clinical case: A 38-year-old woman, experienced palmoplantar pruritus, generalized urticaria, angioedema and conjunctival hyperemia, 30 minutes after the intake of a 5mg folic acid tablet. She was taken to the Emergency Department and on discharge was referred to the Allergy and Clinical Immunology Department, where the patient underwent a diagnostic workup. The Skin Prick Test (SPT) was positive for the 5 mg/mL concentration and the Basophil Activation Test (BAT) was considered positive for both dilutions, from an initial solution concentration of 5mg/ml: 1/100 dil (CD63=9.03%; SI=10.1) and 1/160 dil (CD63=7.46%; SI=8.4). Discussion/Conclusion: We report a patient with an immediate reaction to folic acid with positive SPT and BAT, which favors an IgE-mediated allergy. To our knowledge, this is the first case describing the use of a BAT in the diagnostic workup of folic acid allergy.